Isolated bulbar paralysis in a patient with medullar tau pathology: a case report. Issue 8 (20th June 2010) - Pretnar-Oblak, J; Zaletel, M; Hajnšek, T M; Meglič, B; Hočevar-Boltežar, I; Popović, M
Abstract : Increased morbidity and mortality rates as well as some other manifestations in Alzheimer's disease can be explained by subcortical degeneration. Pathological evidence is scarce but confirmative. We report a 77-year-old patient who presented with a 6-year history of dyspnoea, stridor and dysphagia. Unexpectedly, histopathological examination disclosed extensive degeneration of the medulla by tau pathology. The majority of symptoms and signs could be explained by the medullary tau pathology. Whether the medullary tau pathology in this case was a rare aberrant progression of Alzheimer's disease or a new presentation of tauopathy concomitant with subclinical Alzheimer's disease should be elucidated by additional studies.